2001
DOI: 10.1046/j.1365-2265.2001.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and validity of changes in scores on the Graves' ophthalmopathy quality of life questionnaire (GO‐QOL) after different treatments

Abstract: As a general guideline, one could consider a mean change of at least 6 points on one or both subscales an important change in daily functioning for patients. For more invasive therapies, a change of at least 10 points is recommended as a minimal clinically important difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(158 citation statements)
references
References 11 publications
9
136
1
8
Order By: Relevance
“…12 Orbital decompression can restore appearance and save vision, leading to major improvements in quality of life. 9 The data presented here provide an insight into the current management of patients with Graves' orbitopathy in England. To our knowledge, this is the first geographically based study of orbital decompression.…”
Section: Discussionmentioning
confidence: 99%
“…12 Orbital decompression can restore appearance and save vision, leading to major improvements in quality of life. 9 The data presented here provide an insight into the current management of patients with Graves' orbitopathy in England. To our knowledge, this is the first geographically based study of orbital decompression.…”
Section: Discussionmentioning
confidence: 99%
“…However, overall scores of QOL on the SF-36 were not highly correlated with the severity of disease, probably because the generic QOL questionnaires such as Medical Outcome Study, SF-36, and NEI VFQ were not generated specifically for GO. The GO-specific QOL survey provided by Terwee et al, 7 characterized well the GO-specific conditions that impair the QOL. In this study, we found that GO-QOL scores of Korean patients were significantly correlated with disease severity and inflammatory activity measured by the modified NOSPECS score and CAS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The GO-QOL survey was converted into QOL scores in which 0 corresponds to worst and 100 to no disturbance in visual function and appearance. The same method was used as previously described by Terwee et al 7 We gave the translated GO QOL survey and informed consent to almost all patients who visited our oculoplastic clinic. Patients self-administered the questionnaire during outpatient clinic consultations.…”
Section: Outcome Variablementioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the quality of life at baseline and at the end of the study with the Graves' Orbitopathy Quality Of Life (GO-QOL) questionnaire [24]. The questionnaire was not available in Spanish; therefore it was translated to Spanish and then translated back to English by a native English speaker to assure accuracy.…”
Section: Experimental Designmentioning
confidence: 99%